Farmer and consumer behaviour towards organic vegetables - Divya Vijayan (Department of rural marketing management, College of cooperation, banking and management, 2015)
Organic farming is one of the several approaches found to meet the objectives of sustainable agriculture. The need for organic farming in India arises from non sustainability of agricultural production and the damage caused to ecology through the conventional farming practices. Organic farming practices are based on a maintaining harmonious relationship with nature aiming at the protection of the environment. India being an agriculture based on country has vast opportunities to go ahead in the field of organic farming. However, Currently, India ranks 10th among the top ten countries in terms of cultivable land under organic certification. The total area under organic certification is 4.72 million ha (APEDA 2013-14). This signals that potentials are huge and still it has to move forward. The study entitled “Farmer and Consumer Behaviour towards Organic Vegetables” was conducted with the main objectives to study the behaviour of farmers towards organic vegetable farming, to identify the barriers in the adoption process of organic vegetable cultivation and the constraints in marketing of organic vegetables; to examine the consumers behaviour towards organic vegetables and to identify the determinants of consumer behaviour towards organic vegetables. The study covered three districts representing central Kerala. The districts selected were Thrissur, Palakkad and Ernakulum based on the prominence of vegetable cultivation. Three blocks were selected from each district namely Pazhayannur block of Thrissur district, Elevanchery block of Palakkad district and Moovattupuzha block of Ernakulum district based on purposive sampling and expert opinion of field scientist. Thirty conventional farmers (10 each) from the three selected blocks were selected based on purposive sampling. Six organic farmers certified by INDOCERT were also selected for the study. Twenty consumers from each block were selected as sample respondents through snow ball sampling. Thus the total sample respondents consists of 30 conventional vegetable farmers, 6 certified organic vegetable farmers and sixty vegetable consumers. The objectives of the study were analysed with the help of statistical tools like Percentage analysis, Indices, Rank order scale, Likert scale of summated rating, One way ANOVA, Chi-square, Kendall’s coefficient, Kruskal Wallis test and probit model. Farmer behaviour towards organic vegetable farming is analyzed based on the variables like area under vegetable cultivation, major crop cultivated, mode of sale by farmers, interest in organic farming, and attitude and satisfaction level of farmers. The major crops cultivated by selected farmers include cowpea, snake gourd and bitter gourd .The study revealed that average area and productivity of crops from conventional farming is more. But the net income of organic farmers is more than the conventional farmers. All the selected conventional farmers prefer to sell their vegetables through VFPCK whereas organic farmers prefer direct sale. Majority of the farmers expressed their interest in organic farming but they are willing for only partial conversion by gradually reducing chemical application. The analysis of the attitude of the farmer respondents shows that both conventional farmers and organic farmers have highly favorable attitude towards to the statements related to fertility of soil, environmental friendly, health protecting and the quality of vegetables. Organic farmers have highly favorable attitude towards market demand, practical feasibility and low financial risk and premium price. . But the conventional farmer’s attitude is moderately unfavorable to market demand, practical feasibility and low financial risk. The result of ANOVA shows that there is no difference in the attitude of farmers in three districts. Based on the satisfaction index, study found that certified organic farmers are highly satisfied towards market demand, cultivation practices, availability of inputs, availability of labour and price of organic vegetables whereas, they are highly dissatisfied towards technical assistance provided and institutional support system for organic vegetable cultivation. The major barriers identified by the conventional farmers include disease, pest and weather related losses, high cost of production, huge capital investment, high labour cost, lack of knowledge of organic farming practices and organic certification procedures. On the other hand organic farmers identified pest related production loss, difficulties in getting organic certification, huge investment and lack of institutional support as the major barriers in adoption of organic vegetable cultivation. Major environmental barriers identified by all the selected farmers are the cultivation practices of neighbour farms and non suitability of land. Lack of organic marketing networks and competition with non-organic vegetables are perceived as marketing barriers by conventional farmers. Consumer behaviour towards organic vegetables is analyzed mainly based on their preference, awareness, attitude and satisfaction towards organic vegetables. Consumers have partial awareness towards various features of the organic vegetables. Majority of the consumers have complete awareness regarding availability, quality, nutrient value, health aspects, environment friendliness and price of the organic vegetables. However, they are not at all aware about standards fixed for organic vegetables and its labeling. There is no significant difference in the awareness level among district as per the result of ANOVA. Majority of the respondents (61.67 percent) preferred organic vegetables. Reasons for preference to organic vegetables are lower residues, better value for money followed by hygiene and eco friendly attitude of consumers. Kendall’s W shows perfect agreement among the consumers in the ranking of the variables. The study found that all the selected consumers have highly favorable attitude towards the quality of organic vegetables. They have moderately favorable attitude towards shelf life, nutritional value, environmental friendliness and chemical free features of organic vegetables whereas they have highly unfavourable attitude towards price of the organic vegetables. ANOVA shows difference in the attitude among the consumers of three districts. Based on the Kruskkal Wallis test the differences are mainly on perishability nutritious value conservation of environment and pest free nature of organic vegetables. The level of consumer satisfaction towards organic vegetables revealed that they are moderately satisfied with taste, nutrient value, freshness, eco friendliness, shelf life, value for money and source of information. However they are moderately dissatisfied with price, availability and marketing channels. ANOVA shows significant difference in the level of satisfaction in three districts. Based on Kruskal wallis, the differences are mainly on price, quality, availability, marketing channels, source of information and authenticity of organic nature. The important factors which influence the consumer behaviour towards organic vegetables are price, chemical and pesticide free, eco friendly vegetables, health aspect, availability of vegetables and distance to the market. Value for money and quality factors like nutrient value, more calories, hygiene, taste and freshness are also influencing them to certain extent. Study also revealed that consumer attitude towards organic vegetables is not determined by demographic nature of consumers whereas age is a determinant of the consumer satisfaction towards organic vegetables. Further, study points out that age and education are the determinants of consumer preference towards organic vegetables. As a whole, we could able to conclude that a complete change from conventional farming to organic farming practices is not practically feasible in the present agricultural scenario. The study found that the farmer’s attitude towards organic vegetable cultivation is indifferent. The farmers are not ready for complete change of their farming practice to organic farming especially due to their perception regarding huge investment, low yield and uncertainty in market demand. Moreover, consumers have also expressed their concern about high price of the organic vegetables. The limited in number of certified organic vegetable farmers also shows the reluctance of conventional farmers to enter into organic vegetable farming. Therefore it may be suggested that policy makers may encourage good agricultural practices among farmers by following judicious chemical application rather than focusing on purely organic farming practices. Government may also take measures to provide institutional support by conducting training programme awareness campaign and also by extending financial support. Moreover, the NGO’s, consumer organizations, farmer groups and Kudumbasree units can also come forward to encourage organic vegetable cultivation. It may be suggested that certification of organic products should not be entrusted with private agencies as it practiced now. Government or agencies in the public domain like Kerala Agricultural University can be competent authority for organic certification which will make organic certification accessible for small and marginal farmers.